The impact of drought on forest spring phenology in northern China - Haowen Hu; Pengcheng Xue; Shaodong Huang; Zong Wang; Nina Xiong; Liang Shi; Boyi Liang; Jia Wang (Ecological Indicators)
Global warming is altering ecosystem function and productivity, with changes in vegetation phenology playing a crucial role. These changes are driven not only by rising temperatures but also by the increasing intensity and frequency of extreme events, particularly drought. While the response of the start of the growing season (SOS) to the rising temperature has been widely studied, the mechanisms by which pre-seasonal meteorological drought influence spring phenology in forest ecosystems across different hydroclimatic regions remain poorly understood. We utilized a remote sensing dataset with a spatial resolution of 250 m, integrated with meteorological station data, to examine the response mechanisms of SOS to pre-seasonal drought. This study focuses on four hydroclimatic regions across northern China, providing a comprehensive assessment of regional variations in SOS dynamics. The results revealed that: (1) During the period from 2001 to 2020 forest SOS in humid regions occurs approximately 18 days earlier than in arid regions. SOS in the four hydroclimatic regions showed an average trend of advancement, with an average advancement of 0.31 days per year. (2) The impact of pre-season drought on SOS in forests across four study regions exhibits an intriguing pattern. Short-term pre-season drought significantly influences spring phenology. In humid region, drought causes an advance in the SOS for most areas, whereas in semi-arid region, the forests experience a pronounced delay in SOS due to drought conditions. (3) We further explored the different impact patterns of spring phenology during drought years across various hydroclimatic regions: in humid regions during dry years, SOS is primarily driven by elevated temperatures; conversely, in arid and semi-arid regions, SOS is predominantly influenced by water deficiency resulting from drought conditions. Our findings will enhance the current understanding of ecosystem feedback mechanisms and facilitate the assessment of the capacity of the vegetation to cope with extreme climate change in different regions.